Harnessing the graft-versus-leukaemia effect in acute myeloid leukaemia - Sweeney, C (2021)
Allogeneic haematopoietic stem cell transplantation (allo-SCT) is the best established cellular immunotherapy and is a common treatment for acute myeloid leukaemia (AML). Allo-SCT relies on donor T cells identifying AML cells as foreign and eradicating them, which is known as graft-versus-leukaemia (GvL). Donor T cells recognise AML through interactions between their T cell receptor (TCR) and peptide antigens bound by human leukocyte antigen (HLA) on the surface of AML cells. Despite being administered for over 50 years, our understanding of the AML antigens that elicit a donor T cell response after allo-SCT is very limited.